Antimicrobial resistance and genomic characteristics of Salmonella from broilers in Shandong Province - Zhao, Liyuan; Liu, Gang; Tang, Wenli; Song, Xiangbin; Zhao, Xiaoyu; Wang, Chu; Li, Youzhi; Zou, Ming (Frontiers in Veterinary Science, 2023)
The emergence of multidrug-resistant (MDR) strains of Salmonella, which is a genus of important zoonotic pathogens, has aroused great public health concern worldwide. In this study, 167 strains of Salmonella were isolated from 947 samples from broiler farms, slaughterhouses, and markets in Shandong Province. Antibiotic sensitivity testing was performed, and 70 strains of Salmonella were screened out by whole-genome sequencing (WGS) to evaluate serotypes, antimicrobial resistance genes (ARGs), the prevalence of class 1 integrons, the plasmid carriage rate, and phylogenetic characteristics and for multilocus sequence typing (MLST). The results showed that the 167 isolates showed the highest resistance to ampicillin (AMP, 87.4%), sulfamethoxazole (SF, 87.4%), compound sulfamethoxazole (SXT, 81.4%), nalidixic acid (NAL, 80.2%), and amoxicillin/clavulanic acid (A/C, 77.8%). All the strains were sensitive to meropenem (MEM), and 91.0% of the isolates were MDR strains. We screened a total of 45 ARGs, with the highest detection rate observed for the tetracycline (TET) resistance gene tet (A) (81.4%). A total of 21 types of plasmid replicons were detected in Salmonella, of which IncX1 was the most common (74.3%), and 62.9% of the isolates carried a class 1 integron. In addition, a total of 11 different serotypes were detected, with S. Enteritidis as the predominant serovar, followed by S. Infantis and S. Newport. Twelve different sequence types (STs) were detected, among which ST11 was the main type. There was a strong correspondence between serotypes and STs. We also found that S. Indiana and S. Kentucky had extremely high rates of resistance to ciprofloxacin (CIP) and third-generation cephalosporins. System-wide genome analysis showed the occurrence of long-distance transmission across fields. In conclusion, the detection of multidrug resistance and isolates carrying multidrug resistance genes is the main problem, and emergency strategies should be implemented to address this issue.